POLA KATA JAMA’ TAKSĪR DALAM NOVEL “QĀTILU HAMZAH” KARYA NAJIB KAILANI (ANALISIS MORFOSINTAKSIS - Dena Agustina; Yoyo Yoyo; Mat Taib bin Pa (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2021)
This study aims to describe the word patterns of jama 'takṡīr, grammatical signs, and their function and position in the novel "Qātilu Hamzah" by Najib Kailani morphosyntactic theory. The data collection technique in this study used a descriptive qualitative method with the note-taking method. Meanwhile, the data analysis used descriptive morphosyntactic analysis. Based on the results of the analysis, the following findings were found. First, the pattern of jama 'takṡīr in the novel "Qātilu Hamzah" by Najib Kailani has 63 data consisting of 40 words (1 wazn) jama' takṡīr type jama 'takṡīr qillah, 19 words (6 wazn) jama' takṡīr type jama 'takṡīr kasrah, 4 words (4 wazn) jama 'takṡīr type jama' takṡīr Sigat Muntahā al-Jumū '. Second, based on its position in the sentence (syntax) jama 'takṡīr occupies three syntactic functions: Marfu', Manshub, and Majrūr. Each of these functions is further classified into several divisions including the position of Marfu' functions as Fā'il, naibul Fā'il, mubtada', khabar, ismu kana wa akhwatiha, khabaru inna wa akhwatiha, na'at wal man'ut, aṭaf, taukid, idhofah and badal. Then the position of Manshub functions as maf'ul bih, maf'ul muthlaq, maf'ul liajlih, maf'ul fiih, maf'ul ma'ah, mustatsna bi illa, hal, tamyiz, munaada, khabaru kaana wa akhwatiha, ismu inna wa akhwatiha, na'at wal man'ut, aṭaf, taukid, idhofah and badal. Then finally the position of Majrur served as Majrur bi harfi Jarr, and idhofah.